Carbon nanotube bridges fabricated by laser comb. Issue 20 (14th May 2019) - Wang, Lei; Chi, Xiannian; Sun, Lianfeng; Liu, Qian
Abstract : Laser comb, a novel method to fabricate suspended carbon nanotubes. Abstract : Suspended bridge-shaped carbon nanotube (CNT) has great potential in nano-electromechanical systems, highly-sensitive sensors, various nanodevices and so on. However, complex processing largely restricts its practical applications. This work presents a novel laser comb (Laco) effect, stimulating a simple and effective fabrication strategy to achieve aligned suspended CNTs, which are bridge-shaped, direction-controlled, easily-patterned and all-carbon based. The Laco phenomenon is ascribed to different heat accumulations in two vertical directions under pulse laser-raster scanning (PLrS).